2021
DOI: 10.1098/rsbl.2021.0171
|View full text |Cite
|
Sign up to set email alerts
|

The confounding effects of sub-thermoneutral housing temperatures on aerobic exercise-induced adaptations in mouse subcutaneous white adipose tissue

Abstract: Mice are the most commonly used model organism for human biology, and failure to acknowledge fundamental differences in thermal biology between these species has confounded the study of adipose tissue metabolism in mice and its translational relevance to humans. Here, using exercise biochemistry as an example, we highlight the subtle yet detrimental effects sub-thermoneutral housing temperatures can have on the study of adipose tissue metabolism in mice. We encourage academics and publishers to consider ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…This is consistent with the previous literature demonstrating that the genetic deletion of PGC‐1a in BAT does not affect UCP1 expression 63,64 . There were no effects of chronic MNTH treatment on any transcript in either iWAT (Figure 1L) or eWAT (Figure 1M), and the ability of MNTH to induce UCP1 expression in BAT but not iWAT or eWAT is consistent with a growing body of literature contending the physiological relevance of the browning of white adipose tissue 21,22,65–67 . Importantly, the ability of MNTH to attenuate weight gain without affecting energy intake was preserved in obese mice that had been fed a high‐fat diet for 6 weeks (Figure S2A–C).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with the previous literature demonstrating that the genetic deletion of PGC‐1a in BAT does not affect UCP1 expression 63,64 . There were no effects of chronic MNTH treatment on any transcript in either iWAT (Figure 1L) or eWAT (Figure 1M), and the ability of MNTH to induce UCP1 expression in BAT but not iWAT or eWAT is consistent with a growing body of literature contending the physiological relevance of the browning of white adipose tissue 21,22,65–67 . Importantly, the ability of MNTH to attenuate weight gain without affecting energy intake was preserved in obese mice that had been fed a high‐fat diet for 6 weeks (Figure S2A–C).…”
Section: Resultssupporting
confidence: 91%
“…To date, only one other study has reported topically treating mice housed at a near thermoneutral temperature with MNTH, but unlike our current work at thermoneutrality, this study only made acute thermogenic measures under chow‐fed conditions and interestingly they anesthetized mice with isoflurane, a known inhibitor of BAT thermogenesis, 74,75 prior to each topical MNTH application 54 . More recently, two studies have demonstrated that a high‐fat diet supplemented with MNTH (0.5%–1%) reduced body weight gain over 12–28 weeks in male mice, 31,50 and while this dietary MNTH‐induced attenuation of weight gain was TRPM8‐dependent 31 and associated with increases in UCP1‐dependent thermogenesis, 31,50 both studies housed mice at sub‐thermoneutral temperatures confounding measures of thermogenesis 21,26 . Moreover, food intake was either not reported 50 or was only measured during the first and last week of the 28‐week dietary intervention 31 excluding the possibility that MNTH, which causes a dose‐dependent taste aversion over 50 µg/ml in mice, 55 could have attenuated weight gain via subtle effects on energy intake over time.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations